2015 International Conference on Industrial Engineering and Operations Management (IEOM) 2015
DOI: 10.1109/ieom.2015.7093740
|View full text |Cite
|
Sign up to set email alerts
|

Study of success factors of TPM implementation in Indian industry towards operational excellence: An overview

Abstract: Presently the manufactures are facing a great pressure to reduce cost of manufacturing and provide new and quality products in the market on a regular basis. The India's manufacturing sector is striving hard towards operational excellence. Reduction of waste, improvement of quality, higher through put and overall more efficient production system is leading India towards a manufacturing revolution. A good number of companies have started implementing a range of business strategies including going lean, and usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…Collaborators' resistance related to cultural changes provided by the implementation of TPM. (Ahuja & Khamba, 2008b;Aspinwall & Elgharib, 2013;Attri, Grover, Dev, & Kumar, 2013;Bamber, Sharp, & Hides, 1999;Bartz et al, 2012;Carrijo, 2008;Cigolini & Turco, 1997;Cooke, 2000;da Costa et al, 2015;Estanqueiro & Lima, 2006;Gupta, Vardhan, & Al Haque, 2015;Lawrence, 1999;Milara Guedes, 2009;Poduval, Pramod, & Jagathy Raj, 2015;Rodrigues & Hatakeyama, 2006) 3…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Collaborators' resistance related to cultural changes provided by the implementation of TPM. (Ahuja & Khamba, 2008b;Aspinwall & Elgharib, 2013;Attri, Grover, Dev, & Kumar, 2013;Bamber, Sharp, & Hides, 1999;Bartz et al, 2012;Carrijo, 2008;Cigolini & Turco, 1997;Cooke, 2000;da Costa et al, 2015;Estanqueiro & Lima, 2006;Gupta, Vardhan, & Al Haque, 2015;Lawrence, 1999;Milara Guedes, 2009;Poduval, Pramod, & Jagathy Raj, 2015;Rodrigues & Hatakeyama, 2006) 3…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Collaborators' deficit understanding the philosophy, principles and tools that compose the TPM program. (Ahuja & Khamba, 2008b;Aspinwall & Elgharib, 2013;Attri et al, 2014Attri et al, , 2013Baglee & Knowles, 2010;Bamber et al, 1999;Carrijo, 2008;da Costa et al, 2015;Gupta et al, 2015;Lawrence, 1999;Milara Guedes, 2009; P.S. Poduval et al, 2015;Rodrigues & Hatakeyama, 2006;Singh et al, 2016) 6…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Ma et al [36] reported that TPM increases production system efficiency, brings social benefits, and promotes management systems in production departments. On the other hand, Gupta, Vardhan, and Haque [13] mention that TPM increases employee morale and skills, improves the use of technology, and enhances equipment working conditions and customer satisfaction. Additionally, successful industries that implement TPM increase their overall equipment efficiency (OEE) by 30%, and some have increased OEE by 95%.…”
Section: Tpm Benefitsmentioning
confidence: 99%